ONLINE LEARNING DURING THE COVID-19’S EPIDEMIC OF HIGHER EDUCATIONAL INSTITUTIONS IN CHANTHABURI PROVINCE - Kaewponthong, Supitchaya; Yeamsoontron, Pachabodee (Journal of Graduate MCU KhonKaen Campus, 2021)
The purpose of this research was to 1) study the characteristics of the online learning during the COVID-19’s epidemic of higher educational institutions in Chanthaburi province 2)analyze the conditions of the instruction system from the crisis COVID-19’s epidemic of higher educational institutions in Chanthaburi province and 3) present an online learning model for higher educational institutions during the crisis COVID-19’s epidemic in Chanthaburi province This study conducted both a quantitative and qualitative methods and the subjects in this study consisted of 390 who selected from 12 programs, the lecturers and undergraduate students who studied at Rambhai Barni Rajabhat University and Mahachulalongkornrajavidyalaya University, Academic Service Unit, Faculty of Social Sciences Phutthamonthon, Chanthaburi Province, which selected by using the table of taro Yamane and simple random sampling. The instrument for gathering data was a questionnaire. The statistics used to analyze the data were frequency, percentage and mean. The questionnaire and the interview analyzed by content analysis and descriptive. The findings were as follows. The programs applied for online learning at Rambhai Barni Rajabhat University and Mahachulalongkornrajavidyalaya University, Academic Service Unit, Faculty of Social Sciences Phutthamonthon, Chanthaburi Province were zoom and Google meet. The lecturers can be chosen according to their needs and ability. The characteristics of the lecturers comprised 5, there were, the personal characteristics, the quality of teaching and learning, the measurement and evaluation, and overall as a high level (= 4.14) Moreover, the Students' self-learning adaptation is divided into 5 areas, namely; self-directed learning, love and want to learn new things, the ability to choose skills for learning, find out the answers for self-learning, and the responsibility for learning and steps to reach the goal. Overall at a high level (= 4.00) There were two online learning models; On-site and Online. These were dependent on 1) planning curriculum 2) learning environment 3) instructional design 4) teaching measurement and evaluation 5) facilities and 6) online teaching strategies.